2009
DOI: 10.1002/jcb.22196
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species‐induced cell death of rat primary astrocytes through mitochondria‐mediated mechanism

Abstract: Astrocytes, the most abundant glial cell population in the central nervous system (CNS), play physiological roles in neuronal activities. Oxidative insult induced by the injury to the CNS causes neural cell death through extrinsic and intrinsic pathways. This study reports that reactive oxygen species (ROS) generated by exposure to the strong oxidizing agent, hexavalent chromium (Cr(VI)) as a chemical-induced oxidative stress model, caused astrocytes to undergo an apoptosis-like cell death through a caspase-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…Both cNOS and NF-B play dual roles in regulation of apoptosis (27,29,30,33,(37)(38)(39). To better understand the roles of cNOS and NF-B in regulation of cell fate after UVB irradiation, we determined the effects of JSH-23 and L-NAME on cell death and recovery after UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cNOS and NF-B play dual roles in regulation of apoptosis (27,29,30,33,(37)(38)(39). To better understand the roles of cNOS and NF-B in regulation of cell fate after UVB irradiation, we determined the effects of JSH-23 and L-NAME on cell death and recovery after UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…NF-B Activation Protects Cell Death Upon UVB RadiationBecause both cNOS and NF-B have dual roles in regulation of apoptosis and cell survival (27)(28)(29)(30), we examined the short term (4 -6 h) and long term (6 days) effects of L-NAME, BAY11-7085, and JSH-23 on cell survival and recovery after UVB irradiation using apoptotic and clonogenic assays, respectively. For the short term effect of 50 mJ/cm 2 UVB irradiation, the irradiation alone decreased the cell survival rate to ϳ85 and 71% at 4 and 6 h post-irradiation, respectively (Fig.…”
Section: Lanes 5 8 and 11 Versus Lane 2)mentioning
confidence: 99%
“…Prolonged exposure to these conditions will induce the formation of reactive O 2 species (ROS), which will eventually kill cells. 5,6 Many methods have been proposed and utilized to improve O 2 delivery in large scale cell culture systems, including redesign of the bioreactor by computational modeling to alleviate mass transfer limitations, and supplementation of O 2 carriers (hemoglobin-based and perfluorcarbon-based) into the cell culture medium to increase the solubility of O 2 in the aqueous medium. Computational fluid dynamics has long been used to design and to optimize bioreactors by simultaneously modeling momentum and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of suffering cells, however, is clearly higher, as demonstrated by directly looking at DNA damage by the comet assay (only ~33% of cells still undamaged at 10 μM arsenite). On the basis of these findings we should have expected an increase of ROS production in treated astrocytes, since on one hand, arsenic is known to induce modifications of ROS levels in other cell types (26), and, on the other, astrocytes are known to respond to certain stress with an increase of ROS production (25,27). However, arsenite treatment did not induce increased ROS levels in astrocytes, but on the contrary a decrease, suggesting the occurrence of some modifications which result in a generally decreased rate of basal metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…It has been demonstrated that arsenic induces decreased locomotor activity and behavioral disorders in exposed male rats (15), and that the effects can be transmitted from the maternal to fetal tissues across the transplacental barrier (14). Astrocytes, the most abundant glial cell population in the central nervous system (CNS), contribute to the establishment of the blood-brain barrier (24, and references therein), and perform functions particularly important in maintaining neuronal viability (25). Moreover, astrocytes form the front line in the brain parenchyma against foreign molecules crossing the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%